pitpβ_w Encoding Phosphatidylinositol Transfer Protein Is Involved in Female Differentiation of Chinese Tongue Sole, Cynoglossus semilaevis - Sun, Yuxuan; Zhang, Mengqian; Cheng, Peng; Gong, Zhihong; Li, Xihong; Wang, Na; Wei, Min; Xu, Xiaodong; Xu, Wenteng (Frontiers in Genetics, 2022)
Phosphatidylinositol transfer protein (pitp) plays important role in phospholipid transfer in animals. However, a pitp variant (pitpβ_w) in Chinese tongue sole was identified by transcriptomic analysis for its female-biased expression. The coding sequence of pitpβ_w was 816 bp, encoding 371 amino-acid protein. pitpβ_w showed female-biased expression, and was relatively high in brain, muscle, and ovary. In different developmental stages of ovary, pitpβ_w could be detected from 40 day until 3 years post hatching, and the highest expression was observed at 90 days. In situ hybridization revealed that pitpβ_w was predominantly localized in early-stage oocyte (I-III stages). After siRNA-mediated knockdown of pitpβ_w in ovarian cell line, the expression of sox9a was reduced, while figla_tv1 and sox9b were significantly increased. Our findings suggest that pitpβ_w might play an important role in female differentiation and early oogenesis by acting as a negative regulator.